Improving the activities of a robotic guide by taking into account human reactions - Rainer, J Javier; López Hernández, Fernando; Galán, Ramón (Data Science and knowledge Engineerign for Sensing Decision Support, 2021)
Traditionally robots are autonomous systems that plan and execute actions without taking into account any external feedback. This paper studies to what extent a robot is able to alter its behavior based on observing a series of positive or negative human reactions. We describe the result of introducing these human reactions in a plan of actions by means of fuzzy logic analysis of the reactions. In this way, the election of the actions to perform is based on a combination of the initial plan of actions and of a fuzzy logic weighting of the utility of previously executed actions.
Ponencia del congreso "13th International Conference on Fuzzy Logic and Intelligent Technologies in Nuclear Science (FLINS)"
Keywords: WOS(2)